Pre-Clinical Investigations of the Pharmacodynamics of Immunogenic Smart Radiotherapy Biomaterials (iSRB) - Michele Moreau; Shahinur Acter; Lindokuhle M. Ngema; Noella Bih; Gnagna Sy; Lensa S. Keno; Kwok Fan Chow; Erno Sajo; Oscar Nebangwa; Jacques Walker; Philmo Oh; Eric Broyles; et al. (Pharmaceutics, 2023)
The use of an immunogenic smart radiotherapy biomaterial (iSRB) for the delivery of anti-CD40 is effective in treating different cancers in animal models. This study further characterizes the use of iSRBs to evaluate any associated toxicity in healthy C57BL6 mice. iSRBs were fabricated using a poly-lactic-co-glycolic-acid (PLGA) polymer mixed with titanium dioxide (TiO2) nanoparticles incorporated into its matrix. Animal studies included investigations of freely injected anti-CD40, anti-CD40-loaded iSRBs, unloaded iSRBs and control (healthy) animal cohorts. Mice were euthanized at pre-determined time points post-treatment to evaluate the serum chemistry pertaining to kidney and liver toxicity and cell blood count parameters, as well as pathology reports on organs of interest. Results showed comparable liver and kidney function in all cohorts. The results indicate that using iSRBs with or without anti-CD40 does not result in any significant toxicity compared to healthy untreated animals. The findings provide a useful reference for further studies aimed at optimizing the therapeutic efficacy and safety of iSRBs and further clinical translation work.